2018
DOI: 10.1016/j.anorl.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Control of vertigo in Ménière's disease by intratympanic dexamethasone

Abstract: Dexamethasone is part of the management strategy for patients with Ménière's disease refractory to conventional treatment, implemented before destructive treatment. It achieves control of vertigo in 70% of patients at 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…They found that 23% of patients were free of vertigo at the end of 24 months after IT steroids, but there was no significant improvement in hearing. These results are in accordance with those from Weckel et al 23 who retrospectively evaluated 25 patients treated with IT dexamethasone; they reported a satisfactory control of vertigo in 92% of the patients, and this protocol achieved control of vertigo in 70% of patients at 2 years. Harcourt et al 24 suggested IT methylprednisolone as an effective treatment for the long-term control of vertigo attacks, without he known inner-ear toxicity associated with gentamicin.…”
Section: Discussionsupporting
confidence: 91%
“…They found that 23% of patients were free of vertigo at the end of 24 months after IT steroids, but there was no significant improvement in hearing. These results are in accordance with those from Weckel et al 23 who retrospectively evaluated 25 patients treated with IT dexamethasone; they reported a satisfactory control of vertigo in 92% of the patients, and this protocol achieved control of vertigo in 70% of patients at 2 years. Harcourt et al 24 suggested IT methylprednisolone as an effective treatment for the long-term control of vertigo attacks, without he known inner-ear toxicity associated with gentamicin.…”
Section: Discussionsupporting
confidence: 91%
“…Other AQPs have been suspected to be involved in the pathogenesis of MD, showing a likely key-role of this type of membrane channels in the pathophysiology of MD [65][66][67] . Beside the evidence of AQP role in the endolymph homeostasis, corticosteroids (which have been shown effective in the treatment of MD [24][25][26][27] ) have already been suspected to act through AQP function, in particular by upregulating mRNA of AQP1 68 , or AQP 3 known to be crucial in the reabsorption of water in the inner ear 69 .…”
Section: Figure 8 Putative Mechanism For Spontaneous Interaction Betw...mentioning
confidence: 99%
“…This approach has shown significant benefits in the treatment of MD [24][25][26][27] . Several mechanisms of action have been put forward to explain the effect of dexamethasone in the treatment of MD, such as an anti-inflammatory effect as in the context of acute peripheral vestibulopathy, or a direct modulation of fluid fluxes at the base of the EH formation 26,[28][29][30] . However, none of these hypotheses have so far been substantiated theoretically and verified by experiment.…”
Section: Introductionmentioning
confidence: 99%
“…It achieves control of vertigo in 70% of patients at 2 years. 16,17 11. Drugs with Probable Efficacy…”
Section: Steroidsmentioning
confidence: 99%